2016
DOI: 10.22161/ijeab/1.4.54
|View full text |Cite
|
Sign up to set email alerts
|

Youth Involvement in Agricultural Production in Obi Local Government Area, Nasarawa State, Nigeria

Abstract: Abstract-This present study was focused on the assessment of youth involvement in agricultural production activities in Obi Local

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…It could be noted that 54.17% of youths had medium level of extension contact and 55.83 per cent of them had moderately favorable attitude towards rural development activities. These findings are supported by the findings of Girei et al [5] Kitturmath et al [6] Bhanu [7].…”
Section: Resultssupporting
confidence: 89%
“…It could be noted that 54.17% of youths had medium level of extension contact and 55.83 per cent of them had moderately favorable attitude towards rural development activities. These findings are supported by the findings of Girei et al [5] Kitturmath et al [6] Bhanu [7].…”
Section: Resultssupporting
confidence: 89%
“…David T. Sun et al (2022) reported that individuals involving in poultry farming were not solely dependent on poultry as main source of income. Girei et al (2016) revealed in his study that 18 per cent believed farming was a means of reducing poverty among them Relationship between independent variables of rural youth with their participation in pig farming activities : It was evident from Table 4 that the variables such as gender, economic orientation, herd size, livelihood It was clear from the data that gender, economic orientation, herd size, livelihood security had infl uence over the participation in pig farming. Rout et al (2020) reported that by involving in agri-allied activities rural youth can add additional income to their family thereby can improve their standard of living and thus infl uenced them to participate in faming activities.…”
Section: Resultsmentioning
confidence: 97%
“…That entails providing a sound background for the up-growing youth to be partakers in agricultural education where they could play their roles effectively. Girei et al (2017) identified several benefits of youth participation in agriculture; and that they possess the latent (physical) energy requirement and ability to participate in all agricultural operations. The authors reiterated that youth have propensity to learn and imbibe new ideas and technologies.…”
Section: Introductionmentioning
confidence: 99%